KEEFEKTIFAN METODE SQ3R TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN PESERTA DIDIK KELAS IV SD NEGERI KARANGLO - Azizah, Amalia Nurul (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2021)
This study aims to determine the effectiveness of the SQ3R method on the ability to read comprehension grade IV students at Karanglo Primary School. The type of this research is True Experimental design with the research design used is Pretest- Posttest Control Group Design. While the research procedure used is using a research model from expert Sugiyono. Research data collection techniques in the form of tests and questionnaires. The results showed that the ability to read comprehension with the SQ3R method was higher than the ability to read comprehension with discussion methods for grade IV students in Karanglo Primary School. This was evidenced from the results of the questionnaire t-test with a significance level of 95% (0.05) obtained t arithmetic (2.575) > t table (2.037) and the results of t-test learning outcomes with a significance level of 95% (0.05) obtained t arithmetic (2.963) > t table (2.037). based on the t value, it can be concluded that the SQ3R method is more effective than the discussion method.